?2-Adrenoceptor Stimulation Restores Frontal Cortex Plasticity and Improves Visuospatial Performance in Hidden-Prenatally-Malnourished Young-Adult Rats - Hernandez-Kunstmann, A; Laurido-Fuenzalida, C; Burgos-Gallegos, H; Constandil-Cordova, L; Saez-Briones, P; Barra-Pezo, R (Academic Press, 2015)
Moderate reduction in dietary protein composition of pregnant rats from 25% to 8% casein, calorically compensated by carbohydrates, has been described as a "hidden malnutrition" because it does not alter body and brain weights of pups at birth. However, this dietary treatment leads to altered central noradrenergic systems, impaired cortical long-term potentiation (LTP) and worsened visuo-spatial memory performance. Given the increasing interest on the role played by β2-adrenoceptors (β2-ARs) on brain plasticity, the present study aimed to address the following in hidden-malnourished and eutrophic control rats: (i) the expression levels of β2-ARs in the frontal cortex determined by immunohistochemistry, and (ii) the effect of the β2 selective agonist clenbuterol on both LTP elicited in vivo in the prefrontal cortex and visuospatial performance measured in an eight-arm radial maze. Our results showed that, prenatally malnourished rats exhibited a significant reduction of neocortical β2-AR expression in adulthood. Concomitantly, they were unable to elicit and maintain prefrontal cortex LTP and exhibited lower visuospatial learning performance. Administration of clenbuterol (0.019, 0.038 and 0.075mg/kg i.p.) enhanced LTP in malnourished and control animals and restored visuospatial learning performance in malnourished but not in normal rats, in a dose-dependent manner. The results suggest that decreased density of neocortical β2-ARs during postnatal life, subsequent to hidden prenatal malnutrition might affect some synaptic networks required to elicit neocortical LTP and form visuospatial memory, since those neuroplastic deficits were counteracted by β2-AR stimulation. © 2014 Elsevier Inc.